Continuous pyrolysis of organosolv lignin and application of biochar on gasification of high density polyethylene - Park, Seyoung; Jae, Jungho; Farooq, Abid; Kwon, Eilhann E.; Park, Eun Duck; Ha, Jeong Myeong; Jung, Sang Chul; Park, Young Kwon (Applied Energy, 2019)
In the pyrolysis of lignin, lignin tends to agglomerate during the feeding stage, and the char produced can expand easily to form foam that prevents continuous operation. To solve this problem, a new bench-scale rotary kiln reactor with alumina balls was used for the pyrolysis of organosolv lignin. Also, a bench-scale fixed-bed reactor was used as a reference reactor to gain an insight on the pyrolysis phenomena from rotary kiln reactor. Compared to the fixed bed reactor, the rotary kiln reactor resulted in a higher yield of organic phase oil with high selectivity to monomeric phenolic compounds. Moreover, a larger amount of CO2 was obtained from the rotary kiln reactor, which strongly suggests that decarboxylation is main deoxygenation path. Furthermore, a char without agglomeration and foaming inside the reactor was generated from the rotary kiln reactor. The catalytic properties of the chars produced from both reactors with nickel impregnation were tested for the gasification of high-density polyethylene to produce H2. Among the four different catalysts (Ni/Rotary Kiln char, Ni/Fixed Bed char, Ni/Al2O3, Ni/Activated carbon) tested, the Ni/Fixed Bed char exhibited the highest yield of H2 (~two times higher H2 generation) from the gasification process of high-density polyethylene. X-ray photoelectron spectroscopy and scanning electron microscopy offers that the high dispersion/distribution of Ni occurred when the fixed bed char was used as a support. All experimental findings from this study significantly suggest that Ni supported on char could be an economically viable catalyst for producing H2 from gasification of high-density polyethylene.
Keywords: Bio chars; Catalytic gasification; Catalytic properties; Continuous operation; Continuous pyrolysis; Economically viable; Gasification process; Without agglomeration; Biochar; Catalytic gasification; Continuous pyrolysis of lignin; High density polyethylene; Hydrogen; Rotary kiln reactor